1295. Activity of SPR206, a Polymyxin B Derivative, Compared to Colistin Alone and in Combination Against Multidrug-Resistant Pseudomonas aeruginosa Strains. (31st December 2020) - Abdul-Mutakabbir, Jacinda C; Nguyen, Logan; Stamper, Kyle; Maassen, Philip; Lev, Katherine; Morrisette, Taylor; Kebriaei, Razieh; Rybak, Michael J
Abstract: Background: The emergence of multidrug-resistant (MDR) Pseudomonas aeruginosa strains, has resulted in the use of previously discarded antibiotics, such as the polymyxins (polymyxin B and colistin (COL)). Consequently, the polymyxins are continually characterized by the cytotoxicity associated with their use. SPR206 is a polymyxin analogue, however the N-terminal lipophilic side chain has been extensively modified, decreasing the potential for adverse events. SPR206 has reduced minimum inhibitory concentrations (MIC) MIC50 and MIC90 in P. aeruginosa strains when compared to COL. The objective of this study was to compare the in-vitro activity of SPR206 to COL both alone and in combination with other antimicrobials against MDR P. aeruginosa. Methods: MIC susceptibility testing was performed against 15 carbapenem-resistant P. aeruginosa strains via broth microdilution. SPR206, COL, aztreonam (AZT) and ceftazidime/ avibactam (CAZ/AVI) were evaluated against the P. aeruginosa strains. Dual therapy and triple therapy combinations, either COL or SPR206-based, were tested against four representative strains in 24h time-kill experiments (TKE). Each antibiotic was tested at both 0.5 and 1x the MIC. A >2 log10 and a >3log10 reduction in CFU/ml were defined as synergistic and bactericidal activity, respectively. Results: The MIC testing revealed a lower range of MIC values for SPR206 compared to all agents tested, including COL, for the 15 MDR P. aeruginosa strains. A mean 2-fold reduction in MIC values was observed when comparing the activity of SPR206 to COL. Neither the SPR206 nor COL+CAZ/AVI combinations presented with synergistic activity in the TKEs. SPR206 or COL + CAZ/AVI +AZT, showed synergistic activity against each strain, irrespective of COL or SPR206 base and the tested concentration. At 0.5x MIC bactericidal activity was observed in two of the strains with either COL or SPR206 + AZT. However, at 1xMIC the SPR206+AZT combination exhibited bactericidal activity, equal to that of the triple therapy regimens, against each strain. Conclusion: The combination of SPR206 with other antibiotic agents showed promise in eradicating MDR P. aeruginosa. Further research is warranted to solidify the role of SPR206 in the current antibiotic armamentarium. Disclosures: Michael J. Rybak, PharmD, MPH, PhD, Paratek (Grant/Research Support)